Unlocking the best timber harvesting operational planning with geospatial technology- log yard predetermination - Jamhuri, Jamaluddin; Kamarudin, Norizah; Ismail, Mohd Hasmadi; Ahmad, Siti Azfanizam (Forestry Department Peninsular Malaysia, 2022)
Determining a log yard is essential in timber harvesting operational planning. Locating a log yard must be suitable, especially in dry and easily drained areas with an even slope. Since the timber harvesting operation with the principles of the selective management system (SMS) is restricted within the production of not more than 1000m elevations and slopes less than 40 degrees, log yard location needs to consider this for the predetermination. In addition, to prevent the river from any sediment or debris from timber harvesting activity, the log yard should be placed at least 40 m from the river buffer. It became challenging to locate a suitable log yard considering the slope, elevation, andminimum river distance. This study was conducted 1) to predetermine a suitable log yard by considering multi-objective functions within a timber harvesting area using Geographically Weighted Regression (GWR) analysis, and2) to ensure the placement of the log yard within a minimum distance of 200 m. Felled timber was collected and placed in the log yard area. As a result, 14 log yards were identified within the timber harvesting area, and the tree distribution was examined as clusters (10.716228 z-score) in spatial autocorrelation Moran's index. It was able to locate the log yard by usingGWR analysis and considering the multi-objective functions besides providing a better solution and improved the efficiency in predetermining the log yard as outlined in forest road guidelines by the Forestry Department Peninsular Malaysia (FDPM). © 2022 Forestry Department of Peninsular Malaysia. All rights reserved.